2010
DOI: 10.1159/000320527
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptors are Coupled to Stimulation of Insulin Secretion from Mouse MIN6 β-cells

Abstract: Endocannabinoid lipids are known to exert orexigenic effects via central cannabinoid CB1 and CB2 receptors, which have also been identified in islet endocrine cells. However, there is no consensus on whether the receptors are expressed by β-cells, nor what effect CB1 and CB2 receptor agonists have on insulin secretion. In the current study we have therefore used the mouse MIN6 β-cell line rather than primary islets, which are heterogeneous clusters of endocrine cells. Cannabinoid receptor and diacylglycerol li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 43 publications
7
49
0
1
Order By: Relevance
“…While several in vitro studies have found increased insulin secretion following CB1 activation (Bermúdez-Silva et al, 2008; Duvivier et al, 2009; Getty-Kaushik et al, 2009; Juan-Pico et al, 2006; Li et al, 2010; Malenczyk et al, 2013; Matias et al, 2006), others found decreases in insulin release (Anderson et al, 2013; Li et al, 2011; Nakata and Yada, 2008). One potential explanation for these discrepancies is that ECs, which are elevated under obese conditions, act on CB1 and it in turn regulates factors, such as incretins, found only in the whole organism that are absent in isolated islet and β cell cultures.…”
Section: Discussionmentioning
confidence: 95%
“…While several in vitro studies have found increased insulin secretion following CB1 activation (Bermúdez-Silva et al, 2008; Duvivier et al, 2009; Getty-Kaushik et al, 2009; Juan-Pico et al, 2006; Li et al, 2010; Malenczyk et al, 2013; Matias et al, 2006), others found decreases in insulin release (Anderson et al, 2013; Li et al, 2011; Nakata and Yada, 2008). One potential explanation for these discrepancies is that ECs, which are elevated under obese conditions, act on CB1 and it in turn regulates factors, such as incretins, found only in the whole organism that are absent in isolated islet and β cell cultures.…”
Section: Discussionmentioning
confidence: 95%
“…For example, stimulation of CB1R and/or CB2R activity using selective agonists applied by static incubation has reported to reduce glucose-stimulated insulin secretion from isolated mouse and human islets (66,93). Contrary to these findings, however, there is also evidence that supports the view that cannabinoid receptor activation may act to potentiate insulin secretion when agonists are applied using a dynamic perifusion flow culture system (73). Therefore, further work will be required to establish which of these models better represents modulation by the ECS in vivo.…”
Section: The Ecs-mitochondrial Axis: a Regulator Of Pancreatic Islet mentioning
confidence: 94%
“…A number of nutrients, hormones, and neurotransmitters have been found to influence glucose-stimulated insulin secretion (GSIS) via G protein-coupled receptors (GPCRs), including GLP-1R, GPR40, GPR120, and CB1/2 [6][7][8][9][10] . Recently, the oleoylethanolamide (OEA)-and lysophosphatidylcholine (LPC)-activated GPR119 was shown to facilitate GSIS.…”
Section: Introductionmentioning
confidence: 99%